2017
DOI: 10.1017/s1049023x17006550
|View full text |Cite
|
Sign up to set email alerts
|

Basic Disaster Life Support (BDLS) Training Improves First Responder Confidence to Face Mass-Casualty Incidents in Thailand

Abstract: Basic Disaster Life Support significantly improves confidence to respond to MCI situations, but nurses and active duty military benefit the most from the course. Future courses should focus on these groups to prepare for MCIs. Kuhls DA , Chestovich PJ , Coule P , Carrison DM , Chua CM , Wora-Urai N , Kanchanarin T . Basic Disaster Life Support (BDLS) training improves first responder confidence to face mass-casualty incidents in Thailand. Prehosp Disaster Med. 2017;32(5):492-500 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
3
2
1
Order By: Relevance
“…Similarly, previous study results have revealed that confidence in PSI [ 32 ] and futurism in STS [ 33 ] significantly influence DTA. In contrast to our results, mass-casualty incident simulation training of ERTNs has shown that stresses associated with the approach-avoidance style alone significantly affect DTA [ 34 ]. DTA aims to distribute medical resources to casualties with higher probabilities of survival.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly, previous study results have revealed that confidence in PSI [ 32 ] and futurism in STS [ 33 ] significantly influence DTA. In contrast to our results, mass-casualty incident simulation training of ERTNs has shown that stresses associated with the approach-avoidance style alone significantly affect DTA [ 34 ]. DTA aims to distribute medical resources to casualties with higher probabilities of survival.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, another study assessed mass-casualty incident situation training of nurses, doctors, and other healthcare workers from general hospitals in Thailand. They found that severity classification stress was significantly influenced by individual approach-avoidance style [ 34 ], which is in contrast with our study. Taken together, our study and previous data highlight that enhanced confidence in PSI, futurism in STS, and the influence of the approach-avoidance style in PSI can improve DTA.…”
Section: Discussioncontrasting
confidence: 99%
“…These critically ill patients with multiple comorbidities are at increased risk of in-hospital morbidity and mortality. Furthermore, CCM plays an essential role in the management of bird flu influenza pandemics, injuries caused by motor vehicle collisions, septic shock and natural disasters (4,5). Therefore, CCM is receiving greater attentions from researchers and healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Para el diseño de nuestro programa formativo, realizamos un proceso de adaptación de las recomendaciones internacionales a las particularidades de nuestro grupo formativo, el entorno docente, los espacios académicos y el material que estaba a nuestra disposición y muy especialmente, la tipología de los discentes. Por otra parte, en relación a la utilidad de los conocimientos de SVB en zonas de conflicto, la literatura nos dice que la confianza de profesionales sanitarios y personal militar aumenta con la realización de cursos para adquirir y refrescar las competencias en soporte vital (9). De este modo cabría esperar que ocurriese lo mismo con cooperantes no sanitarios si adquiriesen esas competencias en SVB.…”
Section: Discussionunclassified